Livestock vaccination programme participation among smallholder farmers on the outskirts of National Parks and Tiger Reserves in the Indian states of Madhya Pradesh and Assam. - Andy Hopker (Public Library of Science (PLoS), 2021)
Effective livestock vaccination has the potential to raise prosperity and food security for the rural poor in low and middle income countries. To understand factors affecting access to vaccination services, and guide future policy, smallholder farmers in three locations in India were questioned about vaccination of their cattle and buffalo, with particular reference to foot and mouth disease (FMD), haemorrhagic septicaemia (HS) and blackquarter (BQ). In the three regions 51%, 50%, and 31% of respondents reported vaccinating their livestock; well below any threshold for effective population level disease control. However, within the third region, 65% of respondents in villages immediately surrounding the Kaziranga National Park reported vaccinating their cattle. The majority of respondents in all three regions were aware of FMD and HS, awareness of BQ was high in the Kanha and Bandhavgarh regions, but much lower in the Kaziranga region. The majority of respondents had positive attitudes to vaccination; understood vaccination protected their animals from specific diseases; and wished to immunise their livestock. There was no significant association between the age or gender of respondent and the immunisation of their livestock. Common barriers to immunisation were: negative attitudes to vaccination; lack of awareness of date and time of vaccination events; and difficulty presenting animals. Poor access to vaccination services was significantly associated with not vaccinating livestock. Fear of adverse reactions to vaccines was not significantly associated with not vaccinating livestock. Respondents who reported that vets or animal health workers (AHWs) were their main source of animal health knowledge were significantly more likely to have immunised their livestock in the last twelve months. Participants cited poor communication from vaccinators as problematic, both in publicising immunisation programmes, and explaining the purpose of vaccination. Where vaccinations were provided free of charge, farmers commonly displayed passive attitudes to accessing vaccination services, awaiting organised "immunisation drives" rather than seeking vaccination themselves. Based on these findings the following recommendations are made to improve participation and effectiveness of immunisation programmes. Programmes should be planned to integrate with annual cycles of: disease risk, agricultural activity, seasonal climate, social calendar of villages; and maximise efficiency for vaccinators. Dates and times of immunisation in each village must be well publicised, as respondents frequently reported missing the vaccinators. Relevant farmer education should precede immunisation programmes to mitigate against poor knowledge or negative attitudes. Immunisation drives must properly engage beneficiaries, particularly ensuring that services are accessible to female livestock keepers, and sharing some responsibilities with local farmers. Payment of a small monetary contribution by animal keepers could be considered to encourage responsibility for disease prevention, making vaccination an active process by farmers.